Strategi Peningkatan Kualitas Pelayanan Kesehatan Melalui Implementasi Sistem Manajemen Mutu ISO 9001:2015 - Kartono Kartono; Purnomo Wirawan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
The aim of this research is to identify strategies that can be implemented to improve the quality of health services through QMS ISO 9001:2015 and their impact on patient satisfaction and operational efficiency. This research uses a qualitative approach with a case study method in several hospitals that have implemented ISO 9001:2015. Data was collected through interviews with management, staff and patients, as well as analysis of documents related to the implementation of SMM. The results of this research show the implementation of Quality Management Principles: Hospitals that implement ISO 9001:2015 principles, such as customer focus and a risk-based approach, experience an increase in patient satisfaction and a reduction in complaints. Staff Involvement Staff involvement in the quality management process through training and feedback sessions has been proven to increase their motivation and commitment to quality standards. Performance Measurement: The use of clear performance indicators allows hospitals to identify strengths and weaknesses in their services, thereby facilitating continuous improvement. Patient Feedback : Hospitals that routinely collect and analyze patient feedback can identify areas for improvement, which has a positive impact on the overall patient experience.  Continuous Improvement: By implementing the PDCA (Plan-Do-Check-Act) cycle, hospitals can ensure that their processes and procedures are always updated and relevant.